The technification of the field in the goian municipalities of agribusiness (Research, Society and Development, 2021)
The territorial and spatial configuration existing in the southwest of the state of Goiás is the result of the numerous historical transformations that have occurred in the micro-region over time. From the production in scale in the Southwest of Goiás, three municipalities become the main areas of agribusiness in Goiás. Guided in three main agroindustrial complexes: grains, meat and sugar-energy. This article analyzes the transformations that occurred in the southwest of Goiás in recent years, especially the municipalities of Jataí and Rio Verde, and the main elements that transformed them in the main municipalities of the agribusiness of Goiás. At the same time the aggravation of the socioeconomic and environmental problems shown by concentration of land, the swelling of cities, the exclusion of groups of small farmers from the target areas of large production, to the detriment of middle and large groups, is observed.